PENGARUH GENDER, TEKANAN KETAATAN, KOMPLEKSITAS TUGAS, PENGALAMAN AUDITOR, PENGETAHUAN AUDITOR DAN KOMPLEKSITAS DOKUMEN AUDIT TERHADAP AUDIT JUDGEMENT (Studi Empiris Pada Badan Pemeriksa Keuangan RI Pusat) - Indah Permata Sari; Desmiyawati '; Susilatri ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The aim of this study was to examine the effect of gender, obedience pressure, task complexity, experience of the auditor, auditor’s knowledge and complexity of the document audit on the audit judgement. The samples in this study were 92 auditors working at the Supreme Audit Agency ( BPK ) RI . The sample was taken by purposive sampling method. Collecting data was taken by questionnare distributed directly to auditors in the Supreme Audit Agency ( BPK) RI . The Respondents are used in the analysis were 80 respondents (86.96%). Data processed out by using a multiple regression analysis using SPSS Version 17. The result of the study found that gender, experience of the auditor, the auditor’s knowledge and the complexity of the document audit have a significanteffect on the audit judgement. while obedience pressure and task complexity have no significant effect on the audit judgement. Based on total adjusted R-Square results proved that on the variabel work gender, obedience pressure, taskcomplexity, experience of the auditor, the auditor’s knowledge and the complexity of the document audit affect the audit judgement results of 78,9% while the rest of 21,1% were affected by other variables that were not performed in this study.Keywords: gender, auditor, knowledge, complexity, and judgement